PENGEMBANGAN METODE PEMBELAJARAN BACA AL-QUR’AN UNTUK MENINGKATKAN KEMAMPUAN LITERASI QUR’ANI PESERTA DIDIK - Pitri Anisa Ritonga Anisa; Hidayat Nur Wahid Hsb Hidayat; Nursaima Siregar Saima; Mudrika Tambunan Rika (Amsal Al-Qur’an: Jurnal Al-Qur’an dan Hadis, 2026)
This study aims to analyze the implementation of Qur’anic reading instructional methods and their effectiveness in improving students’ Qur’anic literacy skills. Employing a descriptive qualitative approach, data were collected through observations, interviews, and documentation in Qur’anic education institutions. The findings reveal that the use of methods such as Iqra’, Baghdadiyah, Tilawati, and Ummi significantly contributes to enhancing students’ fluency, accuracy of pronunciation, and understanding of basic tajwīd principles. The methods proved effective in making learning more enjoyable and relevant, reducing dropout rates in Qur'anic studies. However, challenges such as resource availability and teacher training were noted. This study contributes to educational pedagogy by offering practical strategies for Islamic education, emphasizing the need for continuous adaptation to modern contexts. Future research should explore long-term impacts and scalability across diverse cultural settings. Despite these positive outcomes, the study highlights the need for continuous innovation, particularly through the strengthening of pedagogical strategies, improving teacher competence, and integrating digital learning media to support independent practice. This research is expected to serve as a valuable reference for the development of Qur’anic reading education in both formal and non-formal learning environments, contributing to more effective and sustainable literacy programs.